Citrullinemia Type I - A Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Citrullinemia type I (CTLN1) is an inherited urea cycle disorder where the enzyme argininosuccinate synthetase is deficient. It can lead to recurrent hyperammonemic crisis that may result in permanent neurological sequelae, even death. Vomiting in patients with urea cycle disorders may either be the result or cause of acute hyperammonemia, particularly if due to an illness that leads to catabolism. Therefore, age-appropriate common etiologies of vomiting must be considered when evaluating these patients. We present a case of a 2 year 5 month old female child with CTLN1 who had a history of frequent vomiting after the age of one year and some recent neurological manifestations like excessive crying and lethargy and one episode of unconsciousness. Investigations revealed high level of ammonia. Amino acid profile using tandem mass spectrometry showed markedly increased plasma level of citrulline. After administration of sodium benzoate and protein restricted diet there was dramatic improvement of all the symptoms.J Bangladesh Coll Phys Surg 2015; 33(2): 98-100